Teachers’ Beliefs in Teaching Reading towards National Examination Challenge in Indonesia - Intan Kusumawardhani; Erwin Suhendra (LPPM Universitas Bumigora Mataram, 2018)
Reading is an important skill to be acquired in second language learning. The significance of teaching reading is aimed at educating students to face life. However, the existence of national examination as a measurement standard brings some effects towards teachers’ beliefs in teaching reading. Moreover, it is taken as students’ final evaluation to pass the school by 40% percentage from NE and 60% from school. The soul of teaching reading to get students’ comprehension of texts can be damaged since people are thinking more pragmatic. Teachers tend to change their way in teaching reading when the national examination day is closer. This research will be conducted descriptively, using questionnaire and interview as the research instruments. In order to face the newest curriculum in Indonesia, NE is pondered as good to be held as the measurement of education in Indonesia, but the side effects in teaching reading should be taken as consideration. This paper also aims at finding out solution for betterment of education.